English-French Code Mixing in The Chocolate Thief Novel - Dea Eka Pratiwi; Putu Weddha Savitri; Putu Lirishati Soetama (Lembaga Pengembangan Kinerja Dosen, 2025)
Nowadays in the era of globalization, many people use two languages in communication and it is called bilingualism. Bilingualism occurs when speakers and listeners mix languages. This situation is known as code mixing. Code mixing is the use of more than one language in one sentence. Code mixing is not only used in direct communication but also in writing, for example in literature and especially in novels. The phenomenon of code mixing occurs in the novel The Chocolate Thief by Laura Florand. The aims of this study to identify the types of code-mixing and to find out the factors of code mixing used by Laura Florand in The Chocolate Thief novel. This study employs a descriptive qualitative method. The data were collected through documentation and note-taking techniques, focusing on narration and utterance of the characters in the novel which contain English France code mixing. The collected data were analyzed by applying Muysken’s theory about the types of code mixing, which includes insertion, alternation, and congruent lexicalization. It also applies Bathia and Ritchie's theory to find out the factors for code mixing, which includes participants roles and relationship, situational factors, message instrinsic factors, and language attitude, dominance, and security. The finding of this study, there are three types and four factors of code mixing. This novel was used code mixing in narration and character utterances. There are three types used, namely insertion, alternation, and congruent lexicalization. Insertion is the most frequently used type. The factors for using code-mixing can be determined from the types of code-mixing used by Laura Florand. From the research findings, four factors were identified, participants roles and relationships, situational factors, message intrinsic factors, and language attitudes, dominance, and security.